Green Synthesis Of Silver Nanoparticles From Stylosanthes Hamata (L.) Taub. Characterization And Its Antimicrobial Potential - Mukeshbabu. N; Mary Kensa V (Revista Electronica de Veterinaria, 2024)
Among various noble metal nanoparticles, silver nanoparticles (AgNPs) have garnered significant attention due to their unique characteristics, including excellent electrical conductivity, chemical stability, as well as catalytic and antibacterial properties. The green synthesis of silver nanoparticles utilizing plant extracts rich in phytochemical compounds has gained widespread interest. This eco-friendly method is not only more biocompatible and cost-effective but also holds potential for large-scale production. The present study approved the ability of Stylosanthes hamata (L.) Taub. Plant extract for the synthesis of silver nanoparticles for the first time. The green synthesis silver nanoparticles were characterized using a UV-visible spectrophotometer, Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray analysis (EDX). The synthesized silver nanoparticles exhibited a crystalline structure with spherical shaped along with some irregular shapes with an average size of 5 to 100 nm. and a maximum absorbance at 422 nm. The synthesized silver nanoparticles were evaluated for antimicrobial activity. The result showed that the silver nanoparticles of S. hamata effectively inhibited Klebsiella pneumonia, Lactobacillus acidophilus, Staphylococcus aureus, and Pencillium notatum growth with a maximum inhibition zone of 16 mm, 16mm, 14 mm, and 13 mm, respectively. The study demonstrates the effectiveness of S. hamata in the green synthesis of silver nanoparticles, which exhibited notable antimicrobial activity. This research underscores the potential of plant-mediated synthesis for developing eco-friendly antimicrobial agents.